Antisense Oligonucleotide Inhibition of Apolipoprotein C-III Reduces Plasma Triglycerides in Rodents, Nonhuman Primates, and Humans - Graham, Mark J.; Lee, Richard G.; Bell, Thomas A.; Fu, Wuxia; Mullick, Adam E.; Alexander, Veronica J.; Singleton, Walter; Viney, Nick; Geary, Richard; Su, John; Baker, Brenda F.; Burkey, Jennifer; et al. (Circulation research, 2013)
RATIONALE:Elevated plasma triglyceride levels have been recognized as a risk factor for the development of coronary heart disease. Apolipoprotein C-III (apoC-III) represents both an independent risk factor and a key regulatory factor of plasma triglyceride concentrations. Furthermore, elevated apoC-III levels have been associated with metabolic syndrome and type 2 diabetes mellitus. To date, no selective apoC-III therapeutic agent has been evaluated in the clinic. OBJECTIVE:To test the hypothesis that selective inhibition of apoC-III with antisense drugs in preclinical models and in healthy volunteers would reduce plasma apoC-III and triglyceride levels. METHODS AND RESULTS:Rodent- and human-specific second-generation antisense oligonucleotides were identified and evaluated in preclinical models, including rats, mice, human apoC-III transgenic mice, and nonhuman primates. We demonstrated the selective reduction of both apoC-III and triglyceride in all preclinical pharmacological evaluations. We also showed that inhibition of apoC-III was well tolerated and not associated with increased liver triglyceride deposition or hepatotoxicity. A double-blind, placebo-controlled, phase I clinical study was performed in healthy subjects. Administration of the human apoC-III antisense drug resulted in dose-dependent reductions in plasma apoC-III, concomitant lowering of triglyceride levels, and produced no clinically meaningful signals in the safety evaluations. CONCLUSIONS:Antisense inhibition of apoC-III in preclinical models and in a phase I clinical trial with healthy subjects produced potent, selective reductions in plasma apoC-III and triglyceride, 2 known risk factors for cardiovascular disease. This compelling pharmacological profile supports further clinical investigations in hypertriglyceridemic subjects.